A study of relationship between various platelet indices and outcome of dengue fever in pediatric patients - Mangshetty, Roopa; A. B., Apurva; Harwal, Shweta (International Journal of Contemporary Pediatrics, 2023)
Background: The study analyzed clinical characteristics and platelet indices in 200 children (1 month to 15 years) diagnosed with dengue fever, admitted to affiliated hospitals. It aimed to explore the relationship between platelet indices and disease severity in pediatric patients of teaching hospitals affiliated with MRMC College with a confirmed diagnosis of dengue fever. Methods: In this study, the majority of patients were aged (10-15) years, with a small percentage (3.5%) being infants. Females accounted for 50% of the cases. Fever was the most common symptom, followed by headache, abdominal pain, and myalgia. Rash occurred in (14.5%) of cases. Among 200 cases, 80 exhibited warning signs, with varying positivity for NS1 and IgM. All patients required fluid therapy, and (77.5%) needed ICU care. Platelet count and Plateletcrit decreased initially but improved later, while PDW, MPV, and PLCR increased and then decreased. NS1-positive cases had lower platelet count and Plateletcrit but higher PLCR and MPV compared to IgM-positive cases. Results: The study found that lower platelet count and Plateletcrit, as well as higher mean platelet volume, were associated with more severe disease outcomes, including longer hospital stays, increased intensive care unit care, and higher fluid therapy requirements. However, there was no significant correlation between other platelet indices (PLCR and PDW) and disease severity indicators. Conclusions: In conclusion, this study provided valuable insights into the clinical features and platelet indices of patients with dengue fever. Understanding the relationship between these indices and disease severity can help in predicting the progression of the illness and improving patient management strategies.